Thermal requirements and estimate of the number of generations of biotypes "corn" and "rice" of Spodoptera frugiperda - Busato, Gustavo Rossato; Grützmacher, Anderson Dionei; Garcia, Mauro Silveira; Giolo, Fabrizio Pinheiro; Zotti, Moisés João; Bandeira, Juliana de Magalhães (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to evaluate the effect of the temperature on the biology of the biotypes "corn" and "rice" of Spodoptera frugiperda (J.E. Smith, 1797) (Lepidoptera: Noctuidae) and to estimate the number of generations per year in laboratory and field. Caterpillars of four populations of S. frugiperda were collected in Rio Grande do Sul State, Brazil, identified by electrophoresis as the biotypes "corn" and "rice" in isolated areas (spaced for more than 300 km), areas of corn and irrigated rice production, as well as in adjacent areas that produces corn and rice irrigated side by side. The most appropriate temperature for the development of the two biotypes was 25ºC. In laboratory, a number between 11.0 and 11.3 generations year-1 for the biotype "corn" can be obtained, originating from isolated and adjacent areas, respectively, and, for the biotype "rice", 12.1 and 12.2 generations year-1 when originating from isolated and adjacent areas, respectively. In the field, the occurrence of 8.3 and 6.1 generations year-1 for the biotype "corn" was estimated, respectively, in isolated and adjacent areas and 8.4 and 7.0 generations year-1 for the "rice" biotype, respectively, in isolated and adjacent areas. In adjacent areas, the "rice" biotype presents an extra generation per year in relation to the "corn" biotype.